FAKTOR-FAKTOR YANG MEMENGARUHI STRUKTUR MODAL PERUSAHAAN MANUFAKTUR GO PUBLIC - Muhammad - Ridho (Jurnal Ekonomi Dan Bisnis, 2019)
This study aims to determine the effect of profitability, liquidity level, company size, business risk, growth opportunity, managerial ownership, asset structure on the capital structure of manufacturing companies in the Indonesia Stock Exchange (IDX). The type of data used is secondary data in the form of financial statements that are officially published through www.idx.co.id and the company's official website. The technique used for sampling companies in this study is to use a purposive sampling method with predetermined criteria. The sample of this researcher amounted to 172 samples. The analytical method used in this study is a multiple linear regression analysis method using the classical assumption test. The results showed that profitability (ROA) partially had a negative and not significant effect on Capital Structure (DER), Liquidity Level (CR) partially had a negative and significant effect on Capital Structure (DER), Company Size (SIZE) partially positive influence and not significant to capital structure (DER), Business Risk partially has a negative and not significant effect on Capital Structure (DER), Growth Opportunity (GROWTH) partially has a positive and significant effect on Capital Structure (DER), Managerial Ownership (DMOWN) is partially influential positive and not significant to Capital Structure (DER), Asset Structure (SA) partially has a negative and significant effect on Capital Structure (DER).